1976
DOI: 10.3382/ps.0551513
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine, Acid, and Heat Treatments to Eliminate Salmonella on Broiler Carcasses

Abstract: A high agitation prechill treatment with 50 p.p.m. chlorine and 1% succinic acid at 55° C. (131° F.), plus two stage simulated commercial chilling with 50 p.p.m. chlorine, eliminated Salmonella typhimurium which had been inoculated on broiler carcasses before treatment and chilling, but carcass appearance was damaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…The combination of succinic acid exposure with heat treatment was shown by Cox et al (1974b) to retard poultry spoilage, but it resulted in bleached skin and a "cooked" appearance. Thomson et al (1976) found similar results with a combination of chlorine and succinic acid at 55 C.…”
Section: Introductionsupporting
confidence: 64%
“…The combination of succinic acid exposure with heat treatment was shown by Cox et al (1974b) to retard poultry spoilage, but it resulted in bleached skin and a "cooked" appearance. Thomson et al (1976) found similar results with a combination of chlorine and succinic acid at 55 C.…”
Section: Introductionsupporting
confidence: 64%
“…Water or chemical spraying has been proposed as a practical method for controlling bacterial contamination during poultry processing (Li et al, 1995;Mulder, 1993;Smulders, 1987;Thomson et al, 1976;Whitehead et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Thomson et al (1976) showed that chlorine (50 mg/l), when added to an immersion pre-chill treatment, was effective at preventing cross-contamination of carcasses with Salmonella. Similarly, Bailey et al (1986) found that using chlorine (40 mg/l) in wash water could combat bacteria present on a chicken and reduce the presence of Salmonella by 96 per cent, compared with a 50 per cent reduction when using an unchlorinated water spray.…”
Section: Risks Of Poultry Meat and Chlorinementioning
confidence: 99%